Design and development of a smart supermarket system – Microsoft Imagine Cup 2022 (C) - Tan, Justin Koon Han (Nanyang Technological University, 2022)
Food waste is a pervasive problem in the twenty-first century, made worse by increased household stockpiling during the Covid-19 pandemic. If left unchecked, food waste will become a growing problem. Despite the enormous benefits of technology, consumer-level food waste has not seen creative and impactful solutions. This project investigates the use of current machine learning technologies, such as an OCR model, in conjunction with a smartphone application to develop a concept that assists consumers with household food management. Current solutions to consumer-level food waste include ineffective government-led awareness campaigns and application-level solutions that are insufficient as some measures targeting lifestyle. As such, the purpose of this project is to develop an effective and practical smartphone application that will integrate seamlessly into a user's grocery shopping lifestyle and contribute to the reduction of food waste. This project was submitted to the Microsoft Imagine Cup 2022 competition, and this report will focus on my part of the project, which is the backend component, including the RESTful APIs and database implementation.